Let f r ( x ) , g r ( x ) , h r ( x ) be polynomials defined for r ∈ { 1 , 2 , 3 } such that f r ( a ) = g r ( a ) = h r ( a ) for each and every r ∈ { 1 , 2 , 3 } .
Let another polynomial F ( x ) be defined as:
F ( x ) = ∣ ∣ ∣ ∣ ∣ ∣ f 1 ( x ) g 1 ( x ) h 1 ( x ) f 2 ( x ) g 2 ( x ) h 2 ( x ) f 3 ( x ) g 3 ( x ) h 3 ( x ) ∣ ∣ ∣ ∣ ∣ ∣
Find F ′ ( a ) .
Notations: F ′ ( x ) denotes the first derivative of F ( x ) .
Clarification:
Each and every r ∈ { 1 , 2 , 3 } means that for any r chosen from the set { 1 , 2 , 3 } , f r ( a ) = g r ( a ) = h r ( a ) . Such as, f 1 ( a ) = g 1 ( a ) = h 1 ( a ) , f 2 ( a ) = g 2 ( a ) = h 2 ( a ) and f 3 ( a ) = g 3 ( a ) = h 3 ( a ) respectively.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
Since , F ( x ) = ∣ ∣ ∣ ∣ ∣ ∣ f 1 ( x ) g 1 ( x ) h 1 ( x ) f 2 ( x ) g 2 ( x ) h 2 ( x ) f 3 ( x ) g 3 ( x ) h 3 ( x ) ∣ ∣ ∣ ∣ ∣ ∣ then F ′ ( x ) = ∣ ∣ ∣ ∣ ∣ ∣ f 1 ′ ( x ) g 1 ( x ) h 1 ( x ) f 2 ′ ( x ) g 2 ( x ) h 2 ( x ) f 3 ′ ( x ) g 3 ( x ) h 3 ( x ) ∣ ∣ ∣ ∣ ∣ ∣ + ∣ ∣ ∣ ∣ ∣ ∣ f 1 ( x ) g 1 ′ ( x ) h 1 ( x ) f 2 ( x ) g 2 ′ ( x ) h 2 ( x ) f 3 ( x ) g 3 ′ ( x ) h 3 ( x ) ∣ ∣ ∣ ∣ ∣ ∣ + ∣ ∣ ∣ ∣ ∣ ∣ f 1 ( x ) g 1 ( x ) h 1 ′ ( x ) f 2 ( x ) g 2 ( x ) h 2 ′ ( x ) f 3 ( x ) g 3 ( x ) h 3 ′ ( x ) ∣ ∣ ∣ ∣ ∣ ∣
and putting x = a reveals that two rows are identical in each of the determinants so the answer is 0